Mr. Penguin and the fortress of secrets - Smith, Alex T. (London : Hodder Children's Books, 2018)
Aspiring Professional Adventurer Mr. Penguin, his colleague, Colin the spider, and friends Edith and Gordon crash-land on a snowy mountain where they face an evil hypnotist and seek missing pets.
Kirkus Review
Library Media Connection
Kirkus Review, July 2019
Library Media Connection, November 2019
3-6
English.
Keywords: Adventure stories; Detective and mystery stories; Hypnotism -- Juvenile fiction; Lost articles -- Juvenile fiction; Penguins -- Juvenile fiction; Pets -- Juvenile fiction; Spiders -- Juvenile fiction; Adventure and adventurers -- Fiction; Hypnotism -- Fiction; Lost and found possessions -- Fiction; Mystery and detective stories; Penguins -- Fiction; Pets -- Fiction; Spiders -- Fiction; Adventure fiction; Hypnotism -- Fiction; Lost and found possessions -- Fiction; Mystery fiction; Penguins -- Fiction; Pets -- Fiction; Spiders -- Fiction; Action and adventure fiction; Detective and mystery fiction